Seminaire Bourbaki - Seminaire Bourbaki vol 1995/96, exposes 805-819; Seminaire Bourbaki , 1995-96 (Paris Societe Mathematiques de France, 1997)
As in the preceding volumes of this seminar, one finds here fifteen survey lectures on topics of current interest : one lecture on spaces of operators, one on the classification of -algebras and one on spectral geometry ; one lecture on group actions on trees, one on the cohomology of spaces of automorphic forms and one on orbital integrals on certain symmetric spaces ; one lecture on an application of logic to algebraic geometry and one on the resolution of singularities in algebraic geometry ; one lecture on quantum cohomology and one on subriemannian geometry ; one lecture on a mathematical aspect of image analysis and finally two on characteristic classes.
Keywords: C*-algebras